If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+(x-3)+(x+3)+3(x+3)-1=87
We move all terms to the left:
x+(x-3)+(x+3)+3(x+3)-1-(87)=0
We add all the numbers together, and all the variables
x+(x-3)+(x+3)+3(x+3)-88=0
We multiply parentheses
x+(x-3)+(x+3)+3x+9-88=0
We get rid of parentheses
x+x+x+3x-3+3+9-88=0
We add all the numbers together, and all the variables
6x-79=0
We move all terms containing x to the left, all other terms to the right
6x=79
x=79/6
x=13+1/6
| p2–46p=0 | | 4+5x=3x-20 | | x-17=98 | | (4x+2)(4x-10)(5x-11)=540 | | P=20x+55 | | (4x+2)(4x-10)(5x-11)=540 | | 7-10x=2x-29 | | 1.25(x+8)=45 | | 2(u-2)-6u=-12 | | 4x+7=4x+7= 4x+64x+6 | | 24-6r=4r+7 | | 42+87+3y=180 | | x-5=5x-23 | | x-5=5x-23 | | 722=v | | k^–30k=0 | | 1b/4=2½ | | k2–30k=0 | | 1/4b=2½ | | m/2=10.1 | | x/8x3=19 | | (3/2)x+5=14 | | 28=37-x | | n/25=42 | | 6=1/5n | | 6=1n/5 | | 5(x•6)=100 | | 500x10000= | | 5/7c+2=4/7 | | P+18p=6 | | 1=1y+36 | | 0.3x-240,000=0.1x |